2013
DOI: 10.3389/fnhum.2013.00345
|View full text |Cite
|
Sign up to set email alerts
|

Generalization Gradients in Cued and Contextual Pain-Related Fear: An Experimental Study in Healthy Participants

Abstract: Increasing evidence supports the notion that pain-related fear plays a key role in the transition from acute to chronic pain. Recent experimental data show that associative learning processes are involved in the acquisition of pain-related fear. An intriguing yet underinvestigated question entails how spreading of pain-related fear in chronic pain occurs. In a voluntary movement paradigm in which one arm movement (CS+) was followed by a painful stimulus and another was not (CS−) in the predictable group and pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 37 publications
2
40
0
Order By: Relevance
“…Subsequently, participants were required to make novel movements that were either proprioceptively related or unrelated to the original "painful" movement CS. It was found that fear significantly generalized over this proprioceptive dimension (see also, Meulders, Vandebroek, Vervliet, & Vlaeyen, 2013).…”
Section: Perceptual Fear Generalizationmentioning
confidence: 83%
“…Subsequently, participants were required to make novel movements that were either proprioceptively related or unrelated to the original "painful" movement CS. It was found that fear significantly generalized over this proprioceptive dimension (see also, Meulders, Vandebroek, Vervliet, & Vlaeyen, 2013).…”
Section: Perceptual Fear Generalizationmentioning
confidence: 83%
“…The strength of this response follows a gradient which depends on how closely these stimuli match with each other (Vlaeyen, ). Although these concepts were initially based on research in anxiety disorders (Dymond, Dunsmoor, Vervliet, Roche, & Hermans, ), Meulders et al showed that in a predictable pain context, pain‐related fear also spreads to movements that are proprioceptively similar to the original painful movement, and that this generalization does indeed follow a gradient (Meulders, Vandebroek, Vervliet, & Vlaeyen, ; Meulders & Vlaeyen, ). Therefore, we hypothesized that the lumbar ROM during lifting would also, but less strongly, be predicted by the scores on pictures of the PHODA‐SeV that are proprioceptively related to a lifting manoeuver with a bent back.…”
Section: Discussionmentioning
confidence: 99%
“…Replicating previous research, we observed that following successful differential fear acquisition, the strength of the fear response and pain expectancy to a novel unfamiliar movement was proportional to the resemblance of that movement with the original pain‐provoking movement (CS+) and the movement predicting the absence of pain (CS−). The more closely the novel movement resembled the original pain‐provoking movement, rather than the movement predicting the absence of pain, the greater the conditioned response (e.g., fear and pain expectancy) (Honig and Urcuioli, ; McLaren and Mackintosh, ; Lissek et al., ; Meulders et al., ; Geschwind et al., ). We extend previous knowledge in showing that low inhibitory capacity is associated with slower rates of extinction of generalized fear of movement‐related pain and pain expectancy.…”
Section: Discussionmentioning
confidence: 99%